Analisis Pendapatan, Beban Operasional dan Profitabilitas pada PT Samarinda Prima Property Periode Tahun 2013-2015 - Yosephine Rose Christianti; F. Defung; Herry Ramadhani (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
In this paper, the rationale is income, operating expenses and profitability. The purpose of this study was to determine how the role of revenue and operating expenses in PT Samarinda Prima Property in generating the company's profit from the year at 2013 to 2015. To analyze the data, the authors used a comparative analysis tool and also trend analysis to see a comparison of revenue and operating expenses each year, and profitability by proxy, net profit margin, operating profit margin, gross profit margin, return on equity and return on assets. From these results, it can be concluded that the Revenue, Operating Expenses and Profitability in PT Samarinda Prima Property in 2013-2015 tended to decrease. Management of Operating Expenses that are not effective and efficient result in instability of the profitability of the company in achieving corporate goals.Keywords: Revenues, Operating Expenses, trend analysis, comparative analysis of return on assets, return on equity, net profit margin, operating profit margin, gross profit margin